Malaria in Africa - Webb, James L. A., Jr. (History compass, 2011)
This essay surveys the distinctive contours of the long history of malarial infections and interventions in tropical Africa, from the development of heavier patterns of disease transmission during the eras of the Bantu expansions through the contemporary malaria control campaign. It discusses the patterns of interactions of tropical Africans with non-immune foreign populations, efforts at mosquito control, the early history of malaria therapeutics, the first era of synthetic insecticides and new chemical therapies (1945-1962), the retreat from malaria control and the resurgence of infections, and the second era of malaria control (1995 to the present).